Synthesis of Metal Nanoparticles by Microorganisms - Kato, Yugo; Suzuki, Michio (Crystals (Basel), 2020)
Metal nanoparticles (NPs), with sizes ranging from 1–100 nm, are of great scientific interest because their functions and features differ greatly from those of bulk metal. Chemical or physical methods are used to synthesize commercial quantities of NPs, and green, energy-efficient approaches generating byproducts of low toxicity are desirable to minimize the environmental impact of the industrial methods. Some microorganisms synthesize metal NPs for detoxification and metabolic reasons at room temperature and pressure in aqueous solution. Metal NPs have been prepared via green methods by incubating microorganisms or cell-free extracts of microorganisms with dissolved metal ions for hours or days. Metal NPs are analyzed using various techniques, such as ultraviolet-visible spectroscopy, electron microscopy, X-ray diffraction, electron diffraction, energy-dispersive X-ray spectroscopy, and X-ray photoelectron spectroscopy. Numerous publications have focused on microorganisms that synthesize various metal NPs. For example, Ag, Au, CdS, CdSe, Cu, CuO, Gd2O3, Fe3O4, PbS, Pd, Sb2O3, TiO2, and ZrO2 NPs have been reported. Herein, we review the synthesis of metal NPs by microorganisms. Although the molecular mechanisms of their synthesis have been investigated to some extent, experimental evidence for the mechanisms is limited. Understanding the mechanisms is crucial for industrial-scale development of microorganism-synthesized metal NPs.